Modifying adjuncts - Fabricius-Hansen, Cathrine 1942-; Lang, Ewald 1942-2013; Maienborn, Claudia 1963- (Interface explorations, 2003)
Unlike the notion of »argument« that is central to modern linguistic theorizing, the phenomena that are commonly subsumed under the complementary notion »adjunct« so far have not attracted the attention they deserve. In this volume, leading experts in the field present current approaches to the grammar and pragmatics of adjuncts. Among other things, the contributions scrutinize the argument-adjunct distinction, specify conditions of adjunct placement, discuss compositionality issues, and propose new analyses of event-related modification. They are meant to shed new light on an area of linguistic structure that is deemed to be notoriously overlooked